On the Relationship between the Danish Stock and Bond Market in the Medium and Long Term - Jan Overgaard Olesen; Ole Risager (Copenhagen Business School (CBS), Department of Economics, 2000)
This short paper studies the empirical relationship between realized stock returns and bond yields at the 5- and 10-year investment horizons, respectively. Using annual Danish data since 1927, we find that stock returns and bond yields are closely linked in the medium and long term, as we estimate strong cointegrating relations at both horizons. Hence, at the 5- and 10- year investment horizons a high bond yield tends to go hand in hand with a high stock return, and vice versa. Results show that stock returns tend to respond less than one-to-one to changes in the bond yield.
hdl:10398/7619
Keywords: E40; G10; G30; H10; 330; stock returns; Bond yields; Denmark